PENGARUH PAD, DB, INVESTASI DAN TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI SUMUT 2015-2018 - Tamba, Eraima Wati; Surbakti, Yomi Ibrena Br; Sitohang, Melvasari; Malau, Yois Nelsari (2020)
This study aims to determine the effect of local revenue, balanced funds, investment, labor on economic growth in the province of North Sumatra. The types of data used in this study are secondary data, time series and cross-sectional data from districts / cities from 2015-2018. The sampling technique used was the saturated method with 33 districts / cities as respondents. The analytical method used in this research is to use linear data regression using the help of the SPSS 22 for windows program. The results showed that local revenue has a significant positive effect on economic growth. Balanced funds do not have a significant positive effect on economic growth. Investment does not have a positive and significant effect on economic growth. Labor has a significant positive effect on economic growth. Simultaneously, local revenue, balanced funds, investment, labor have an effect on economic growth in the province of North Sumatra.